2014
DOI: 10.4161/epi.29007
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically regulatedMIR941andMIR1247target gastric cancer cell growth and migration

Abstract: These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…miRs can promote or inhibit the development and progression of human cancer (4,5). Deregulation of certain miRNAs, such as miR-10b, miR-29a, miR-145, miR-126, miR-133, miR-143, miR-148a, miR-218, miR-941, miR-1247 and miR-145, have been reported to be associated with gastric carcinoma (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). miR-145 has been shown to generally act as a tumor suppressor in numerous types of human cancers, such as colorectal cancer, gastric carcinoma, bladder cancer and glioma (14,(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…miRs can promote or inhibit the development and progression of human cancer (4,5). Deregulation of certain miRNAs, such as miR-10b, miR-29a, miR-145, miR-126, miR-133, miR-143, miR-148a, miR-218, miR-941, miR-1247 and miR-145, have been reported to be associated with gastric carcinoma (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). miR-145 has been shown to generally act as a tumor suppressor in numerous types of human cancers, such as colorectal cancer, gastric carcinoma, bladder cancer and glioma (14,(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant miRNA expression affects the initiation and progression of carcinogenesis, and is associates with abnormal cell proliferation, differentiation, growth, apoptosis and invasion (15). Recent advances in epigenetics have revealed that miRNA dysregulation frequently occurs in various types of neoplasm, including gastric, colon, lung and prostate cancer, as well as OS (1620). The focus of a vast number of studies on determining the expression of miRNAs in clinical samples has identified an association between miRNA function and oncogenesis or tumor suppressor genes, which was dependent on the function of the miRNA target genes (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetically regulated miR-941 and miR-1247 are transcriptionally silenced by DNA hypermethylation. Their target mRNAs include KDM6B, TAOK1, PRDM16, RARA, STX1B, and RCC2 in gastric cancer cell lines [37]. miR-34c-5p targets 3' UTR of MAPT and the expression of miR-34c-5p is highly reduced by promoter methylation in the multidrug-resistant gastric cancer cell line, SGC-7901/VCR, and paclitaxel-resistant gastric tissues [38].…”
Section: Mirna Targets In Gastric Cancermentioning
confidence: 99%